The Conceptual Report on South American Citizenship: Free human mobility, identity and rights for the citizens in UNASUR - Hidalgo Tandazo, Ramiro (2018)
This document details the steps taken by the UNASUR working group on this subject to prepare the Conceptual Report on South American Citizenship, along with the agreements and the future projections on the matter. It also intends to show the determined work carried out by the South American countries, in which Ecuador plays an active role, to strengthen a regional integration process that will endow its citizens a series of rights and whose final goal is the construction of the “Patria Grande” (Great Homeland) to which people aspire.